A HISTORY OF VIOLENCE: THE CULTURE OF HONOR AND HOMICIDE IN THE US SOUTH. Issue 5 (30th July 2014) - Grosjean, Pauline
Abstract The paper tests the popular hypothesis that the high prevalence of homicide in the South of the United States originates from the settlement by herders from the fringes of Britain in the 18th century. I find that historical Scots‐Irish presence is associated with higher contemporary homicide, particularly by white offenders, and that a culture of violence was transmitted to subsequent generations—but only in the South and, more generally, where historical institutional quality was low. The interpretation is that the Scots‐Irish culture of honor prevailed and persisted as an adaptive behavior to weak institutions. As institutional quality converged between the South and North over the last 200 years, the influence of the culture of honor has been fading over time. The results are robust to controlling for state fixed effects and for a large number of historical and contemporary factors, as well as to relying on instrumental variables for historical settlements. The results are also specific to a particular type of homicide and background of settlers.